STRATEGI GURU PAI DALAM MENANAMKAN NILAI-NILAI KARAKTER PESERTA DIDIK DI SMP LAB SCHOOL FIP UMJ - Widya Ciptani (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The background of this research is built upon the crucial role of Islamic Religious Education (PAI) teachers in addressing the moral challenges of the younger generation, as well as the need for appropriate strategies to instill character values, particularly in junior high schools, which represent a critical transitional period in students’ personality formation. This study is also motivated by the author’s concern over the current condition of students, who often show a lack of good manners and modesty, and are negatively influenced by poor social interactions, the adverse impacts of social media, insufficient parental guidance, the weakening of the education system, and the lack of affection and care. These circumstances prompted the researcher to explore students’ needs in terms of character formation, in order to address this concern and contribute to improving and developing efforts to foster students’ character in schools. The purpose of this study is to examine the strategies implemented by Islamic Religious Education teachers in instilling character values in students at SMP Lab School FIP UMJ, to identify which character values are being instilled, and to explain the supporting and inhibiting factors in the implementation of these strategies. The study specifically aims to describe the strategies of PAI teachers in cultivating character values among students at SMP Lab School FIP UMJ. This research employed a qualitative approach using a case study method. Data collection techniques included observation, in-depth interviews, and documentation. The subjects of this research were PAI teachers and students at SMP Lab School FIP UMJ. The data obtained were analyzed descriptively using qualitative methods, which involved data reduction, data display, and drawing conclusions. The results of the study show that Islamic Religious Education (PAI) teachers at SMP Lab School FIP UMJ employ various strategies in instilling character values, including integrative approaches in the learning process, role modeling through attitudes and behavior, habituation of positive values within the school environment, as well as providing motivation and spiritual guidance. The dominant character values instilled include religiosity, discipline, responsibility, tolerance, and cooperation. These strategies have been proven effective in shaping students’ character and personality.